Republic of Mozambique: Final Report General and Provincial Assembly Elections - European Union Election Observation Missionn (European Union Election Observation Mission, 2019)
On 15 October, Mozambicans elected the president, members of the Assembly of the Republic, members of the 10 provincial assemblies, and 10 provincial governors. Although there was a considerable number of participants, including recently registered political parties, the electoral process was dominated by the three main parties: the ruling Mozambican Liberation Front (FRELIMO), the main opposition Mozambican National Resistance (RENAMO), and the Mozambican Democratic Movement (MDM)
Keywords: G - Mozambique / Moçambique; L - english / inglês; electoral geography / geografia eleitoral

Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Scenarios for Violence in the Resource-rich Cabo Delgado Province - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
The government of Mozambique has a rapidly shrinking window within which to implement a more comprehensive and effective strategy to weaken the Ahlu Sunna wa Jama (ASWJ) insurgents in Cabo Delgado and prevent the group from becoming an entrenched, long-term security problem. This report projects that the security situation in Cabo Delgado will most likely deteriorate during the next 18 months if the ASWJ insurgency continues to recruit new fighters and maintains a high frequency of attacks, as they have done since October 2017. Another key destabilizing factor is a government response that prioritizes military action over community development programs as its primary line of effort against the group. The government’s heavy-handed counterinsurgency approach risks further alienating the local population, driving them to lend active and passive aid to the militants. While the complete pacification of the group is unlikely during the next 18 months, a concerted whole-of-government approach would help undercut the group’s momentum. This includes outreach to the local community, programs, and policies designed to address specific grievances, and the use of targeted military operations. Maputo’s partners in the international community and private sector also have an important role to play. They can leverage their political influence and financial resources to press the Mozambican government to shift its current approach toward one that addresses the underlying grievances driving the insurgency. In doing so, Maputo and its partners have a better opportunity to not only undercut the present violence but potentially prevent future armed groups from emerging.
Keywords: G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; security / segurança; ⛔ No DOI found

Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique - Khadiagala, Gilbert M.; Manhique, Jorge R. (WFD - Moçambique, 2019)
The inclusion of persons with disabilities is an essential element of a strong democracy and a just society. Persons with disabilities (PWDs) being included means that they have a full and equal opportunity to participate in society and in political decision-making processes, to develop their capacities, and to contribute to national progress Like everywhere, persons with disabilities in Mozambique face physical, social, economic and/or environmental barriers to participation. For example, 17 percent of persons with disabilities in Mozambique have been refused entry into a school or preschool because of their disability. Prior to its ratification of the International Convention on the Rights of People with Disability (ICCPD), which protects and promotes the rights and dignity of persons with disabilities, Mozambique had already pioneered progressive measures to promote the inclusion of persons with disability through specific principles in the Constitution of the Republic and the development of multisectoral plans on disability. Furthermore, the Mozambican Government proposed a new set of commitments that were presented at the London Summit in July 2018, reaffirming its adherence to the International Convention on the Rights of People with Disability. The Mozambican Minister for Gender, Children and Social Action, Her Excellency Cidália Manuel Chaúque Oliveira, today spoke at an event on 18th December to launch the study, ‘Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique.’ The study is the result of consultations with people with disabilities of different types and other stakeholders working to promote the rights of persons with disabilities (PWDs) in the Nampula, Beira and Maputo regions of Mozambique. The consulations aimed to find out about the socio-economic and political situations of PWDs and the barriers they face, as well as propose solutions to those problems. The consultation is part of the effort to establish a National Agenda for greater social, economic and political inclusion of PWDs in Mozambique. The study identifies the opportunities for, progress made, obstacles to, and consensus on national policies and strategies. It articulates a ways forward for building an inclusive society and achieving social justice. The study contibutes to Mozambique’s efforts work effectively towards national and international commitments to inclusive development. The study was undertaken as part of the Commonwealth Partnership for Democracy (CP4D) programme. It was carried out by WFD Mozambique in partnership with the Mozambican Association of People with Disability (ADEMO), the Mozambican Forum of Associations for People with Disability (FAMOD), and the Assembly of the Republic of Mozambique, in collaboration with the Ministry of Gender, Children and Social Action and with the technical advice of the Centre for Human Rights of the University of Pretoria in South Africa.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Final Evaluation Report - “Improving oversight in Mozambique's governance” (2016-2019) - FCG International Ltd (FCG International Ltd, 2019)
An external evaluation of the project was conducted in April - May 2019. It looked into the strategy, performance and attainment of the general development goals. The results of the evaluation will be taken into account in the planning of a possible second phase of the project. According to the evaluation, the project is highly relevant both for the strategic partnership between Finland and Mozambique, as well as for the sustainability and inclusiveness of the economic growth arising from the extractive industries and the development of democratic governance. Finnish discretionary government transfers are used to support the Improving Oversight in Mozambique’s Governance 2016–2019 project, which aims to strengthen parliamentary oversight of the management of natural resources in Mozambique. It is a joint project of three organisations; Netherlands Institute for Multiparty Democracy (NIMD), Political Parties of Finland for Democracy (Demo Finland) and Instituto para Democracia Multipartidária from Mozambique (IMD). The project was launched in Mozambique in 2017 and it will be closed at the end of 2019; with a budget of EUR 1,500,000. The evaluation emphasises that strengthening parliamentary oversight is a long-term objective. The project has managed to reach preliminary results in a short time frame in that, for example, Members of Parliament have a better understanding of the challenges met by the extractive industries, and for the first time in Mozambique, there is regular exchange of information and cooperation between national and provincial parliaments. However, performance is not on a sustainable foundation. Sustainable impacts require that a greater number of MPs are trained and the training and research centre of Parliament and the technical secretariats of the provincial parliaments are strengthened. In addition to capacity building, the Parliament should be strengthened by creating wider partnerships and networks with other actors in society. In order to consolidate the results of the project and to improve their sustainability, the evaluation strongly recommends the Ministry for Foreign Affairs to continue the project in cooperation with the new Parliament, which will be elected in October 2019, and with provincial parliaments. It would be useful for the new MPs starting their work at the beginning of 2020 that they make use of the materials produced during the project and consult the MPs who were trained during the project. Additionally, the evaluation recommends the Ministry for Foreign Affairs to continue the project with the same partners, because they have managed to establish well-functioning and confidential relations with the Parliament and other political actors.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; decentralization / descentralização; governance / governação

Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Publisher: Routledge
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Limits of gender equality: Poor, uneducated Mozambicans less likely to see improvement - Bhoojedhur, Sadhiska; Isbell, Thomas (AFR Barometer, 2019)
Gender equality is enshrined in Mozambique’s Constitution and promoted through its participation in international conventions and treaties as well as its 2004 Family Code, which requires equality in property and family law, including sharing of assets within marriage (International Federation for Human Rights, 2007; UN Women, 2012). During the launch of a National Plan of Action on Women, Peace, and Security in June 2018, the Minister of Gender, Children, and Social Welfare reiterated the government’s commitment to promoting gender equality, emphasizing that equal participation of men and women in all spheres of society is a prerequisite for sustainable development (AllAfrica, 2018). Yet gender disparities are a persistent reality for many women in Mozambique, in forms ranging from child marriage and teen pregnancy to domestic violence and sexual abuse (Cumbe, Materula, Sadler, & Agosta, 2017; Christensen, 2018). According to a United Nations Country Team report (2013), more than half of Mozambican women report having suffered some form of physical, sexual, or psychological violence, and almost three-fourths of girls said they were aware of cases of sexual abuse and harassment in their schools. Mozambique ranks 138th out of 164 countries on the United Nations Development Programme’s (2018) Gender Development Index, and especially in the North and in rural areas, traditional patriarchal values remain strong (Tvedten, 2011). In leadership roles, Mozambican women are better represented than women in many other African countries: 40% of the Mozambican Parliament are women (World Bank, 2018). However, while the Global Gender Gap Report ranked Mozambique No. 1 in Africa in 2008 in terms of economic participation and opportunity, by 2018 the country had dropped to No. 7 (No. 49 in the world) because of setbacks in women’s labour-force participation, particularly in senior and managerial positions (World Economic Forum, 2008, 2018). According to the latest Afrobarometer survey, a majority of Mozambicans think gender equality has been achieved with regard to education, work, and land, and give the government good marks on promoting opportunities for women. However, poor and lesseducated citizens are considerably less likely to perceive progress on gender equality. Moreover, Mozambicans’ support for equality is uneven: While most endorse equality in access to land and political leadership, majorities prioritize men when it comes to getting a job and say families are better off if a woman, rather than a man, takes care of home and children.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; poverty / pobreza

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Sah, Anjali; Le, Ha (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies (IDS)-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to US$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

Hiring of Foreigners in Mozambique - Regulatory Regimes and Practices - JICA (Agency for Promotion of Investment and Exports (APIEX), 2019)
The laws and regulations for hiring foreign nationals have been enacted with the aim of protecting the national workforce, ensuring the availability of jobs for them, while limiting employment of foreigners to those positions with levels of technical and professional skills and qualifications which are either nonexistent or insufficient in the country. Historically, the main instrument used by the Mozambican Government to achieve foreign investment promotion balanced with national employment, was the hiring of foreign employees through the quota mechanism, which is still in use at present. In the present context, it is fundamental that the regime of hiring foreign labour allows for certain flexibility but at the same time does not compromise the structural principle of protecting the local labour force. This document is prepared to provide the current regulatory framework for hiring of foreign nationals, as a reference mainly for foreign investors considering employing foreigners in their projects in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego

The State of ICT in Mozambique 2018 - Gillwald, Alison; Mothobi, Onkokame; Rademan, Broc (Research ICT Africa, 2019)
Mozambique has a challenging path ahead if it is to realise the full potential of the ICT sector in developing its economy and to make progress on the information communication technology targets that are intended as enabling the achievement of the United Nations’ Sustainable Development Goals. Mozambique’s successes include licensing and regulatory achievements in telecommunications, which have stimulated competition and contributed to meeting national policy objectives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

Implement - Outcome Harvesting|Civicus - CIVICUS (CIVICUS, 2019)
Outcome Harvesting is a M&E methodology used to identify, describe, verify and analyses the changes brought about by a campaign, support or advocacy initiative (see Better Evaluation or Winter School 2019 presentation by Outcome Mapping Learning Community). In Outcome Harvesting, one collects evidence of change (‘outcomes’ – e.g. changed policy, amended or stopped legislation processes, a new coalition formed, shifted voting behaviour) and then works backwards to assess contribution to that change. Please note that the change can also be a negative change, and/or the change cannot be linked to one’s own contributions but rather to those of other actors. It may be referred to as Outcome Mapping methodology. However, in Outcome Harvesting, there are also other methodologies used during the harvest process. Outcome harvesting can be used for ongoing monitoring throughout a project or programme, in order to produce real-time information on change. It can also be used with evaluation or impact assessments during projects or programmes, at the end of a project, or some time after they have been completed. Outcome Harvesting involves participation with different stakeholders. According to Wilson-Grau (2015) participation is described by the methodology’s main developer as necessary for a successful outcome harvesting process and product. Moreover, it is considered most useful under three conditions (see Ricardo Wilson-Grau and Heather Britt 2012): Focus on outcomes rather than activities: It is not designed to assess whether activities were carried out according to plan, rather than assessing what has changed and why. Complex programming contexts: Outcome Harvesting is suitable for complex programming context where the relationship between the cause and the effects is not fully understood. Examples of complex situations could include in areas such as advocacy, mobilization, capacity development, empowerment or network development. Monitoring and evaluation: Outcome Harvesting can also be used when the purpose as an M&E exercise is to learn about the change and understanding why those changes occurred.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Rules of the Game: An Introduction to the Standards-Related Work of the International Labour Organization - International Labour Organization (International Labour Organization, 2019)
The Rules of the Game: An introduction to the standards-related work of the ILO provides a brief presentation of the ILO’s standards policy with a view to facilitating understanding and ownership by the ILO’s traditional constituents, as well as the United Nations system, non-specialists and the broader public. In its first section, the publication recalls the underlying reasons for and utility of the ILO’s standards-related action at both the national level and in the current context of globalization. The content of international labour standards is then presented thematically in the second section. The third section consists of a description of the supervisory mechanisms of the application of international labour standards by ILO member States. The updating of this reference work, which was first published in 2005 and the most recent edition of which is dated 2014, bears witness to the dynamic nature of the ILO’s standards policy. The new 2019 edition, which coincides with the ILO’s centenary, describes recent developments, including the new instruments adopted, the launch of the Standards Centenary Initiative, which is intended to strengthen the supervisory system, and the establishment of the Standards Review Mechanism. It also places in perspective the essential contribution of international labour standards to the 2030 Sustainable Development Agenda adopted by the Member States of the United Nations in 2015, and the more general reflection on the Future of Work. This edition, prepared by Eric Gravel, of the International Labour Standards Department, contributes to promoting the Organization’s standards-related action and disseminating more broadly information on its standards-related mandate.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; employment / emprego

The Health Budget: The Disparity Between Political Discourse and Practice - N'weti (N'weti, 2019)
Key Messages: - Health is a human right and is constitutionally protected in Mozambique; - The health sector is considered a priority sector by the Government of Mozambique; - The health sector is amongst the least funded by the State Budget in the past four years, (with less than 8% on average), against the 15% assumed in Abuja; - For the year 2014, of the 762.8 million USD allocated to the health sector, 44% came from external sources (REO MOH, 2014). The combined PROSAUDE resources, and the speci c "off-budget" projects’ funding demonstrates the enormous reliance on external partners to support the country’s health strategy; - There is an urgent need to increase internal State Budget funding for the health sector to ensure sustainability.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; budget / orçamento; health / saúde

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia

State Budget Proposal for Fiscal Year 2019 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2019)
Key messages: 1. The envelope of resources for the 2019 State Budget is set to increase to MT 340 billion (from MT 303 billion in 2018), representing Mozambique’s largest nominal budget; however, once factoring in the depreciated currency and high inflation of recent years as well as high debt servicing payments, the purchasing power of this envelope –including for priority sectors– no longer represents a historical high. 2. The share of resources dedicated to investment in Mozambique has been steadily declining, particularly since 2015, due to frozen donor support and a crowding out effect by proportional increases in financial operations and recurrent spending. While in the 2019 Budget Proposal investment has increased to a 30 percent share of total spending, it is still far below the 40 percent norm registered a decade ago. 3. Over the past decade, the share of resources dedicated to the district level has increased at the expense of resources directed to the provincial level; meanwhile central-level expenditure has remained unchanged. In the 2019 Budget Proposal, the central level will, as usual, receive the most resources (64 percent), followed by districts (19 percent), provinces (15 percent), and then municipalities (2 percent). 4. Relative to the Government’s Five Year Plan (PQG), “Priority II: Develop Human and Social Capital” (i.e. priority economic and social sectors) is expected to receive the largest share of funding in the 2019 Budget Proposal. 5. The government has set the goal of allocating at least 60 percent of resources to the priority sectors (according to its methodology of excluding financial operations and debt servicing from the denominator); however, because financial operations and debt servicing have soared as a share of total spending, their 60 percent is no longer a reliable benchmark (e.g. priority sector allocations grew 3.5 times in nominal terms from 2009 to 2019 while the entire budget grew 4 times over the same period) . Proportional priority sector spending as a share of the entire budget (including financial operations and debt servicing) has dropped significantly in recent years. In the 2019 Budget Proposal, it is projected at 51 percent of the entire budget. 6. Among Priority Economic and Social Sectors, Water & Public Works, Transport & Communications, and Agriculture & Rural Development more than doubled their proposed allocations for 2019 relative to 2018 initial allocations. The Education, Health, and Social Action Sectors are also expected to receive a larger allocation than in 2018, but the increase will be smaller. The Infrastructure Sector (mainly the roads sub-sector) will be the only one experiencing a cut in allocation relative to the 2018 Budget.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Publisher: Centro Brasileiro de Análise e Planejamento
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde